2021
DOI: 10.1149/1945-7111/ac42f0
|View full text |Cite
|
Sign up to set email alerts
|

An In-Depth Analysis of the Transformation of Tin Foil Anodes during Electrochemical Cycling in Lithium-Ion Batteries

Abstract: Tin foils have an impressive lithium-storage capacity more than triple that of graphite anodes, and their adoption could facilitate a drastic improvement in battery energy density. However, implementation of a dense foil electrode architecture represents a significant departure from the standard blade-cast geometry with a distinct electrochemical environment, and this has led to confusion with regards to the first cycle efficiency of the system. In this work, we investigate the unique behavior of a tin active … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Observation of the second electrochemical cycle shows this process resulted in a drastic transformation of the reaction kinetics, significantly improving lithium transport throughout the material (Figure c). This alteration in kinetics resulted in a recovery of previously trapped capacity, analogous to the recovery observed for pure tin foils . During subsequent cycling, the generated structure was able to accept lithium at 8 mA cm –2 without any risk of lithium plating (Figure d).…”
Section: Results and Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…Observation of the second electrochemical cycle shows this process resulted in a drastic transformation of the reaction kinetics, significantly improving lithium transport throughout the material (Figure c). This alteration in kinetics resulted in a recovery of previously trapped capacity, analogous to the recovery observed for pure tin foils . During subsequent cycling, the generated structure was able to accept lithium at 8 mA cm –2 without any risk of lithium plating (Figure d).…”
Section: Results and Discussionmentioning
confidence: 70%
“…This alteration in kinetics resulted in a recovery of previously trapped capacity, analogous to the recovery observed for pure tin foils. 19 During subsequent cycling, the generated structure was able to accept lithium at 8 mA cm −2 without any risk of lithium plating (Figure 3d). It is expected that the system would be symmetrically capable of fast-discharge, but this was not tested to avoid the high areal-current electrodeposition of lithium associated with rate-testing of high-loading electrodes in the half-cell form factor.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Heligman and Manthiram have tested 16 different metallic foils and concluded that In, Sn, and Al foils deliver promising capacities as well as formation efficiencies [36]. Some successful demonstrations of In foil [37,38], Sn foil [39][40][41][42][43], and Al foil anodes [43][44][45][46][47][48] can also support their conclusions. Novel alloy strategies using interdigitated eutectic alloys may further be a way to utilize one or more active metals, whilst maintaining some structural supporting matrix [39,49].…”
Section: Current Situation Of Libsmentioning
confidence: 83%